Discreet practices in the city in the example of the covert consumption of “monkeys” - Krajewski, Marek (A mosaic city: The culture-oriented description, 2023)
The article proposes the category of discrete practices, understanding it as social practices that allow individuals to engage in actions of which others should not currently be aware. An example of this phenomenon, which is strongly present in the Polish context, is covertly drinking vodka from small glass bottles, known as “monkeys”, in public spaces. An analysis of that phenomenon allows to demonstrate how specific categories of consumers are excluded from the contemporary city simply because they consume alcohol in an improper manner, place, and time. Despite focusing on the “monkey” bottles, I also show why the category of discrete practices is cognitively functional and how it can help research the contemporary city, privacy, power relation and the processes of individualisation.